Impact of the current level in the development of the telecommunication-information system of the Serbian Armed Forces on the defense of the Republic of Serbia - Beriša, Hatidža A.; Zorić, Olga M. (Vojnotehnički glasnik / Military Technical Courier, 2018)
Information, as one of the important factors of armed conflicts, greatly influences the physiognomy, the direction and the speed of the development of contemporary conflicts. It expresses the availability of knowledge and data necessary for successful command and control at all levels. Its availability reduces the uncertainty in military activity and enables a better assessment of the situation, as well as making relevant decisions in real time. In the paper, the Telecommunications and Information System (TkIS) of the Serbian Armed Forces (SAF) is looked at from several aspects, and the issue of the need for improvement of the existing system, imposed by constant development of information technologies, is being updated. The concept, purpose, structure and level of development of the TkIS are dealt with in the paper, particularly the level of development of the SAF TkIS and its cause-effect relation with the defense of the Republic of Serbia, with a focus on military defense. The aim of this paper is to examine the impact of the Serbian Armed Forces telecommunications and information system on the defense of the Republic of Serbia with the emphasis on military defense, and to point out the need for continuous improvement of the TkIS and continuous education, i.e. adequate and timely training of the personnel for its use for military defense. The importance of the work is in the analyzed state of the Serbian Telecommunications and Information System in relation to the needs of the military defense of the Republic of Serbia in the context of contemporary security challenges.